2021
DOI: 10.47447/tjsm.0502
|View full text |Cite
|
Sign up to set email alerts
|

Professional athletes have higher anxiety levels during COVID-19 outbreak compared to recreational athletes and sedentary people

Abstract: Object ve: Although the COVID-19 outbreak affected almost all the people globally, the number of studies investigating the effects on professional athletes are very low. Therefore, we aimed to examine anxiety levels, mental toughness and daily habits of professional and recreational athletes during the early phase of the pandemic and compare these with sedentary control objects.Mater als and Methods: 634 participants were evaluated in April 2020 with an online survey consisted of sociodemographic data, exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These results are consistent with those obtained in other investigation, which has shown that both non‐athletes and athletes declined in mental health during the COVID‐19 outbreak, and experienced increased risk of depression 6,8 . In the case of high‐level professional AwD, potential reasons for those negative changes include disturbances in everyday training routines, uncertainty regarding the organization of sport events, fear about being infected with SARS‐CoV‐2 before sport competitions, and reduced training opportunities 25,26 . Levels of anxiety varied in a cubic way, while levels of depression increased linearly.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with those obtained in other investigation, which has shown that both non‐athletes and athletes declined in mental health during the COVID‐19 outbreak, and experienced increased risk of depression 6,8 . In the case of high‐level professional AwD, potential reasons for those negative changes include disturbances in everyday training routines, uncertainty regarding the organization of sport events, fear about being infected with SARS‐CoV‐2 before sport competitions, and reduced training opportunities 25,26 . Levels of anxiety varied in a cubic way, while levels of depression increased linearly.…”
Section: Discussionsupporting
confidence: 89%
“…6,8 In the case of high-level professional AwD, potential reasons for those negative changes include disturbances in everyday training routines, uncertainty regarding the organization of sport events, fear about being infected with CoV-2 before sport competitions, and reduced training opportunities. 25,26 Levels of anxiety varied in a cubic way, while levels of depression increased linearly. This is probably due to the fact that anxiety is sensitive to many stressors, whereas depression could have been cumulative.…”
Section: Discussionmentioning
confidence: 99%